Minor characters have their day : genre and the contemporary literary marketplace - Rosen, Jeremy (Literature Now., 2016)
How do genres develop? In what ways do they reflect changing political and cultural trends? What do they tell us about the motivations of publishers and readers? Combining close readings and formal analysis with a sociology of literary institutions and markets, 'Minor Characters Have Their Day' offers a compelling new approach to genre study and contemporary fiction.